(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This scientific article presents the need for a new approach to the formation of social relations, specific features of the development of small business and private entrepreneurship in our country. The purpose of writing this article: organization of entrepreneurial activity and legal and regulatory documents guaranteeing it, non-governmental organizations helping entrepreneurs, development of enterprises and showing their main features. The result: the formation of a new generation of entrepreneurs, owners, who think and act in a new way in society, strengthening the economy of the Republic of Uzbekistan, revealing the main features of small business and private entrepreneurship.